Źródło polskiej pracy socjalnej w teorii pracy społeczno-oświatowej Heleny Radlińskiej - Brenk, Mikołaj (Pedagogika Społeczna Nova, 2023)
The article presents the views of Helena Orsza Radlińska (1879–1954) in the context of the development of Polish social pedagogy. Radlińska is widely recognized as the most important figure in the development of social pedagogy in Poland, and the thesis regarding the topicality of her social thought is shared by many researchers. The article indicates the origin of the basic concepts that are the starting point for contemporary research in the field of social pedagogy: care, assistance, rescue and local environment. The aim of the considerations is an attempt to show the concept of “help” developed by Radlińska in its broad and narrow meaning, and to indicate the area of activity of a social worker, i.e. the local environment along with the entire context of its functioning (the role of leaders, social organizations and associates). The heritage of the Polish creator of the school of social pedagogy is an extraordinary source of inspiration for examining the correct functioning of an individual in his environment – both in the historical and contemporary context. The article is a contribution to in-depth research in this area and due to the volume, many issues have been treated only in passing.